Wojnowo copy of philosophical works of John Damascene and Johann Spangenberg translated by Andrei Kurbskiy - Morozova , Nadezhda (Slavistica Vilnensis, 2019)
The Museum of Icons and Culture of Old Believers in the village of Wojnowo (Warmian-Masurian Voivodeship, Poland) contains a manuscript of the late 19th century containing translations of the philosophical works of John Damascene, Johann Spangenberg and Pseudo-Justin Martyr, as well as two original texts by Andrei Kurbskiy. The investigation of the manuscript showed that the works of John Damascene and Spangenberg in this collection are presented in the translation of Kurbskiy-Obolenskiy. The aim of this work is to determine the structural and compositional features of the translation of the philosophical works of John Damascene and Spangenberg, made in the 1570s. in the circle of Andrei Kurbsky, and on the basis of the identified ones, to find potentially related copies, which could be an antigraph or a photograph of the manuscript from Wojnowo monastery. The study revealed four copies of the translations of Dialectic and Elementary Introduction into Dogmas by John Damascene (and Spangenberg’s Syllogisms), potentially related to Wojnowo codex. At least two of them contain structural and compositional features identical to Wojnowo copy of the Kurbskiy’s translation of Elementary Introduction into Dogmas.